Do Financial Markets Value Quality of Fiscal Governance? - Keita, Kady (IMF Working Papers; Working Paper ;, 2019)
We examine the link between the quality of fiscal governance and access to market-based external finance. Stronger fiscal governance is associated with improvements in several indicators of market access, including a higher likelihood of issuing sovereign bonds and having a sovereign credit rating, receiving stronger ratings, and obtaining lower spreads. Using the more granular information on quality of fiscal governance from Public Expenditure and Financial Accountability (PEFA) assessments for 89 emerging and developing economies, we find that similar indicators of market access are correlated with sound public financial management practices, especially those that improve budget transparency and reporting, debt management, and fiscal strategy.